Efficient synthesis and characterization of Cu2OSeO3 nanoparticles via hydrothermal route. (2nd November 2017) - Manolata Devi, Mayanglambam; Jha, Menaka; Ganguli, Ashok Kumar; Chakraverty, Suvankar
Abstract: Cu2 OSeO3 is a multiferroic material which hosts skyrmionic spin structure in its bulk phase (particle size  >  100 nm). Here, we demonstrate successful synthesis of Cu2 OSeO3 nanoparticles at low temperature by adopting hydrothermal method followed by heat treatment. Our observations suggest that the formation of Cu2 OSeO3 nanoparticles is strongly dependent on various reaction parameters including molar ratio of precursors, pH, solvent, reaction temperature and time of the hydrothermal reaction. Irregular morphologies of the particles have been observed and the average particle size of Cu2 OSeO3 is estimated to be ~40  ±  5 nm, which is comparable to the skyrmion size observed in the bulk phase of Cu2 OSeO3 .